Education and the role of the church in Africa: three relevant aspects - Jansen, C. A. (Koers, 2009)
In this article an attempt is made to provide a grounded basis for expanded church involvement in the provision of formal education, HIV and AIDS education and leadership education in Africa. This is done on the basis of a fundamental reflection on the role of the church in education, as well as a brief analysis of the formal education challenge, the HIV and AIDS challenge and the leadership challenge in Africa.